Data Visualization and Analysis of Engineering Educational Statistics - Siddhaling Urolagin; Ishita Upadhyaya; Afrah Abbas Thakur (International Journal of Advances in Applied Sciences, 2018)
Engineering, is one of the most popular fields of higher education in the modern day woreld. Majority of the students these days opt for engineering as a career, due to the vastness of choices provided by engineering. Mechanical, Electrical, Computer Science, Civil and Biotechnology are the various disciplines and have varying strength in terms of number of students who join a particular discipline. In this research, we have gather data from various published articles about engineering education and carried out the data visualization and analysis using Tableau 9.2. The objective of the analysis is to help the students to make the decision and the choice about discipline of engineering from which particular university would be the most suitable based on the data collected and represented. Various categories of statistics such as number of graduates from a particular university in a particular discipline, and which university had the maximum number of graduates in a certain year will help the students make their decisions about their future in a more easy and a sorted manner.